Grazing alone is not enough to maintain landscape diversity in the Montseny Biosphere Reserve - Bartolomé, J.; Franch, J. (Agriculture, Ecosystems & Environment, 2000)
Conservative land-use over the past few decades has converted the Montseny Biosphere Reserve (Spain) from the original open, patchy landscape to almost continuous woodland. Small ruminant grazing is virtually the only major remaining utilisation activity yet little is known about its role in the changing vegetation of the Reserve. This study was undertaken to determine the effects of current grazing practice on its main vegetation components. Three ﬂocks, composed of sheep and goats, that graze yearlong on three separate ranges in the Reserve were selected for study. The ranges represent the wooded slopes and the shrubby upland (altiplano) in the area. Biomass consumption by the ﬂocks was estimated by calculation of normative requirements for observed production and the botanical composition of the livestock diets over a whole annual cycle was determined by micro-histological analysis of the faeces. Production of herbaceous vegetation was determined by clipping sample quadrats, the production of the woody vegetation was derived from previous work in the Reserve. It was found that grazing removed a very small proportion of the dominant Holm oak (Quercus ilex) on the slopes, and a moderate fraction of the shrubby and herbaceous vegetation on the altiplano. Only the heath tree (Erica arborea), an edible shrub in the woodlands, was relatively heavily grazed. It is concluded that grazing alone is not enough to maintain the open, diverse landscape with its many natural values. As in other northern Mediterranean countries, under-utilisation of these woodlands is becoming a serious problem that is also increasing the ﬁre hazard. Maintaining landscape diversity in the region is a complex challenge that land managers should recognise
Keywords: calluna vulgaris; Erica arborea; mediterranean rangeland; Quercus ilex; small ruminants